Method for producing aluminum nitride powder, aluminum nitride powder and package
Patent Information
- Application Number
- JP2021575722
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-06
- Filing Date
- 2021-01-22
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2041-01-22
AI Technical Summary
【0020】 本発明によれば、従来の燃焼合成法によって得ることができなかった、軽い粉砕(すなわち解砕)により容易に細分化することが可能な塊状物の状態で窒化アルミニウムを得ることが可能である。
Abstract
Description
[Technical field]
[0001] The present invention relates to an industrial production method for aluminum nitride powder useful for sintered bodies. [Background technology]
[0002] Aluminum nitride has excellent properties such as high electrical insulation, high plasma resistance, and high thermal conductivity, and is therefore widely used in insulating heat dissipation substrates, semiconductor manufacturing equipment materials, etc. These are manufactured by adding sintering aids to aluminum nitride powder as necessary, molding it using an organic binder, and then degreasing and sintering it under normal pressure or pressure. When yttrium oxide, a typical sintering aid, is used, it traps the impurity oxygen in aluminum nitride, thereby achieving high thermal conductivity.
[0003] Known common industrial methods for producing aluminum nitride powder include a reduction nitridation method in which a mixture of aluminum oxide powder and carbon powder is heated to high temperatures in nitrogen, and a direct nitridation method in which metallic aluminum is reacted with nitrogen at high temperatures.
[0004] Among them, the direct nitridation method industrially implemented is a method of nitriding metal aluminum by external heating, and the aluminum nitride powder obtained contains coarse particles fused by the heat during the reaction, so it is usually pulverized. Therefore, the pulverization process is likely to increase metal impurities and surface oxygen, and when the sintered body is made, the generation of lattice defects due to these impurities causes a decrease in thermal conductivity. In addition, the shape of the particles obtained by pulverization is irregular, and there is a concern that the moldability is poor.
[0005] On the other hand, aluminum nitride powder obtained by the reduction nitridation method has an average particle size of about 1 μm, fewer coarse particles, and a particle shape that is close to spherical and highly pure, compared to aluminum nitride powder obtained by the direct nitridation method. As a result, it has excellent moldability and sinterability, and when made into a sintered body, it is easy to obtain high thermal conductivity.
[0006] However, the reduction nitridation method requires mixing of carbon with aluminum oxide and decarburization of the remaining carbon, so the direct nitridation method is more advantageous in terms of raw material and energy costs, and since continuous industrial production is also possible, it has been desired that the direct nitridation method be able to produce aluminum nitride equivalent to that produced by the reduction nitridation method.
[0007] Combustion synthesis is known as a direct nitriding method, in which a part of a raw material powder layer made of metallic aluminum is ignited in a nitrogen atmosphere, and the reaction heat generated by the following reaction is propagated to the powder layer, thereby promoting the nitriding reaction to synthesize aluminum nitride.
[0008] Al+1 / 2N2 → AlN-ΔH0 In the reaction equation, [-ΔH0] = 320 KJ / mol, and this heat generation is the driving force for the combustion synthesis reaction.
[0009] Known examples of methods for producing aluminum nitride by the combustion synthesis of metallic aluminum include JP-A-7-309611 (Patent Document 1) and JP-A-2000-16805 (Patent Document 2). These patent documents disclose that aluminum nitride powder and a diluent are added together with metallic aluminum to perform the combustion synthesis.
[0010] Incidentally, Japanese Patent Laid-Open Publication No. 7-81909 (Patent Document 3) discloses a method for producing silicon nitride by combustion synthesis, which describes that in order to prevent the synthesized silicon nitride from being obtained as a strong lump, the bulk density of a mixed powder composed of silicon nitride powder and metal silicon powder, which is a diluent (aggregate), is adjusted to be small. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Japanese Patent Application Publication No. 7-309611 [Patent Document 2] JP 2000-016805 A [Patent Document 3] Japanese Patent Application Publication No. 7-081909 Summary of the Invention [Problem to be solved by the invention]
[0012] However, it has been confirmed that the aluminum nitride obtained by the combustion synthesis method using metallic aluminum has a problem that even if a diluent is used to reduce the bulk density, it is obtained in a state of tightly fused lumps depending on the manufacturing conditions. Therefore, in order to use the obtained aluminum nitride as a raw material for a sintered body, it is essential to crush it, and the generation of easily oxidized fracture surfaces caused by crushing forms an oxide layer on the surface of the aluminum nitride particles, which causes an increase in the oxygen content of the aluminum nitride powder, and when this is used as a raw material and sintered, it is difficult to obtain an aluminum nitride sintered body having the required excellent thermal properties and electrical properties. [Means for solving the problem]
[0013] As a result of extensive research conducted in light of the problems in the prior art, the present inventors have discovered that by carrying out a combustion synthesis reaction using specified aluminum nitride particles as a diluent under specific conditions, aluminum nitride can be obtained as lumps in which primary particles having a particle diameter of several μm are gently aggregated, and that these can be processed into particles of an appropriate size by, for example, mild crushing (hereinafter, this operation will also be referred to as "disintegration") without using crushing media, thereby solving all of the above-mentioned problems, and have thus completed the present invention.
[0014] That is, the method for producing aluminum nitride powder according to the present invention is a method for producing aluminum nitride by a combustion synthesis method using metallic aluminum powder, characterized in that a mixed powder obtained by mixing aluminum nitride powder having an average primary particle size of 3 μm or less as a diluent in a ratio of 150 to 400 parts by mass per 100 parts by mass of metallic aluminum powder is ignited and burned in a nitrogen atmosphere.
[0015] In the above-mentioned production method, it is preferable that the average particle size of the metallic aluminum powder is 1 μm or more and less than 10 μm. Furthermore, the bulk density of the mixed powder is 0.6 to 0.9 g / cm 3 It is preferable that the range is .
[0016] It is preferable that the aluminum nitride chunks obtained by burning are crushed to a size having an average particle diameter of 20 μm or less that exceeds the average primary particle diameter of the aluminum nitride particles constituting the aluminum nitride chunks, and then a part of the crushed aluminum nitride chunks is used as the diluent.
[0017] Furthermore, the mixed powder is mixed with a base area of 0.3 m 2 It is preferable to pack the above heat-resistant materials in a flat box in layers and ignite them to burn the metallic aluminum powder. It is preferable to form a heat insulating layer on the bottom surface of the flat box.
[0018] The aluminum nitride powder according to the present invention is characterized in that it is composed of aluminum nitride primary particles having an average primary particle diameter of 3 μm or less, contains agglomerated particles having a crushing strength of 300 MPa or less, and has an average particle diameter that exceeds the above average primary particle diameter and is 20 μm or less.
[0019] The aluminum nitride powder preferably has a carbon concentration of 300 mass ppm or less. These aluminum nitride powders can be obtained by the above-mentioned manufacturing method. The aluminum nitride powder according to the present invention is preferably packed in a resin packaging bag. Effect of the Invention
[0020] According to the present invention, it is possible to obtain aluminum nitride in the form of agglomerates that can be easily broken down into smaller pieces by light crushing (i.e., crushing), which could not be obtained by conventional combustion synthesis methods.
[0021] The aluminum nitride powder obtained by crushing the aluminum nitride lumps to an average particle size of 20 μm or less, which exceeds the average primary particle size of the aluminum nitride particles that compose them, is an agglomerate of primary particles having an average primary particle size of 3 μm or less, and is characterized by having a low cohesive force (low crushing strength) and an extremely low oxygen concentration due to the small number of active surfaces generated by crushing.
[0022] The aluminum nitride powder of the present invention, which is in such an aggregate state, is less prone to dusting and is easy to handle. Furthermore, even if it is used as a raw material for a sintered body without being crushed, it is easily disintegrated by shearing when mixed with an organic binder, making it possible to carry out sintering with high processing efficiency and production efficiency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Hereinafter, an embodiment of the present invention will be described. Manufacturing method of aluminum nitride powder The metallic aluminum powder itself used as the raw material may be a known or commercially available product. There is no particular limitation on the manufacturing method, and any manufacturing method may be used. There is no particular limitation on the purity of the metallic aluminum powder, but taking into consideration the thermal conductivity of the product, it is usually preferable that the purity is 99.9 mass% or more (however, the oxygen content is not included in the calculation of purity).
[0024] The average particle size of the metallic aluminum powder is usually 1 μm or more and less than 10 μm, and preferably 1.5 to less than 10 μm. If metallic aluminum powder with a large average particle size is used, a large amount of aluminum nitride powder with a large particle size that is difficult to dissolve may remain, while one with a small average particle size is difficult to handle and the metal is easily oxidized.
[0025] The amount of oxygen contained in the metal aluminum powder (oxygen content) may be appropriately set depending on the application of the final product, reaction conditions, etc., but is usually about 0.05 to 1 mass%, and particularly preferably 0.1 to 0.6 mass%. If the oxygen content is less than 0.05 mass%, the metal aluminum powder particles tend to be easily fused together during the reaction, and the supply of nitrogen gas to the powder may be insufficient, resulting in a decrease in the nitriding rate. If the oxygen content exceeds 1 mass%, the oxide film on the particle surface of the metal aluminum powder may inhibit the progress of the nitriding reaction.
[0026] In the present invention, aluminum nitride powder is mixed as a diluent together with the metallic aluminum powder. The average primary particle size of the aluminum nitride powder is desirably 3 μm or less, preferably 2 μm or less. If the average primary particle size of the aluminum nitride powder used as a diluent is larger than the above range, the fusion of the metal aluminum particles or the generated aluminum nitride particles becomes significant during the reaction, and as a result, the obtained aluminum nitride becomes a strong lump, making it impossible to achieve the object of the present invention.
[0027] In the present invention, the aluminum nitride powder used as the diluent is not particularly limited in state as long as the average primary particle size is within the above range. For example, the aluminum nitride powder may be in a dispersed state, in an aggregated state in which the primary particles are aggregated, or in a mixture thereof, without any particular limitation.
[0028] Specifically, aluminum nitride powder obtained by reduction nitridation can be mentioned. The aluminum nitride powder obtained by the reduction nitridation is preferable because it generally contains particles with an average primary particle diameter of about 1 μm in a dispersed state. In addition, it is also a preferable embodiment to use a part of the aluminum nitride powder obtained by the method of the present invention as a diluent. As described later, the aluminum nitride powder can be obtained as agglomerated particles of primary particles with an average primary particle diameter of 3 μm or less, and can be used as a diluent as it is.
[0029] The most preferred embodiment of the present invention is one in which aluminum nitride powder obtained by the reduction nitridation method is used at the start of the reaction, and thereafter, a portion of the aluminum nitride powder obtained by the production method of the present invention is used as a diluent.
[0030] The mixing ratio of the aluminum metal powder and the aluminum nitride powder allows control of the reaction, and it is desirable to mix the aluminum nitride powder at a ratio of 150 to 400 parts by mass, preferably 200 to 350 parts by mass, per 100 parts by mass of the aluminum metal powder. By mixing at this ratio, in combination with the specification of the average primary particle size, the reaction can be sufficiently controlled, aluminum nitride chunks that are easy to crush can be obtained, and production efficiency can be increased.
[0031] In the present invention, the method for mixing the aluminum metal powder and the aluminum nitride powder is not particularly limited and any known mixing method can be used. Mixing methods using a ball mill, a V blender, a ribbon mixer, or the like are common.
[0032] Furthermore, the bulk density of the mixed powder may be appropriately set depending on the particle size of the powder, reaction conditions, etc., but is usually 0.6 to 0.9 g / cm 3 , preferably 0.7 to 0.9 g / cm 3 When the nitrogen gas is in this range, the supply of nitrogen gas to the mixed powder is sufficient, combustion proceeds sufficiently, the amount of unreacted aluminum metal is reduced, and aluminum nitride chunks that are easy to crush can be obtained.
[0033] In the production method of the present invention, in order to promote the chain reaction of the aluminum metal powder, a sufficient amount of nitrogen source necessary for the reaction must be present on the surface of the powder in the area where the reaction proceeds, and therefore the nitrogen-containing atmosphere is preferably an atmosphere containing nitrogen at a pressure of 1.0 to 10 atm, and more preferably 1 to 8 atm. As the nitrogen-containing atmosphere, nitrogen or ammonia, or a non-oxidizing gas containing either of them can be used industrially.
[0034] In the manufacturing method of the present invention, the conditions and method of the combustion synthesis reaction are not particularly limited as long as the mixed powder is used and the nitrogen atmosphere is used. For example, the nitriding reaction can be progressed by igniting a part of the metal aluminum powder contained in a flat box-shaped container made of a heat-resistant material in a pressurized reaction container in which the nitrogen pressure is appropriately adjusted. In this case, in order to keep the nitrogen pressure constant or to prevent the nitrogen pressure from falling below a predetermined pressure, it is desirable to continue the reaction while continuously supplying nitrogen to the reaction container in the atmosphere. In addition, the ignition method is not particularly limited, and any method that can start the combustion synthesis reaction can be adopted. For example, a resistor such as carbon is embedded in the metal aluminum powder and the resistor is heated, a known ignition agent is embedded in the metal aluminum powder and the ignition agent is ignited, and an electron beam or laser is irradiated onto the metal aluminum powder.
[0035] A cooling means may be provided near the reaction vessel to prevent the reaction temperature from rising excessively. The cooling means may be either air-cooled or water-cooled. In order to carry out the present invention industrially, the mixed powder is placed in a reaction vessel having a bottom area of 0.3 m. 2 A preferred embodiment is to use a container having the above surface area, specifically, a flat box made of a heat-resistant material such as carbon. The flat boxes are preferably stacked in layers while securing a space for supplying nitrogen. The mixed powder is then filled into the flat box, which is then ignited to cause a combustion reaction of the metallic aluminum powder.
[0036] The mixed powder packed in the flat box is preferably a powder layer having a thickness of 10 to 80 mm. If the thickness of the mixed powder is within this range, the amount of heat generated is sufficiently higher than the amount of heat dissipated, so that the combustion temperature does not decrease and the nitriding rate does not decrease. In addition, the nitrogen supply from the surface of the powder layer reaches the bottom of the powder layer sufficiently, so that the nitriding rate at the bottom can be increased.
[0037] When the method of the present invention is carried out industrially, the reaction vessel has a bottom area of 0.3 m 2 More than 0.5 to 3 m, preferably 2When using such a large-area reaction vessel, it is preferable to form a heat insulating layer on the bottom surface in order to prevent heat loss from the peripheral wall, particularly the bottom surface, of the vessel and to efficiently propagate the reaction heat in the mixed powder.
[0038] The material constituting the heat insulating layer may be any material as long as it is not involved in the reaction. Specific examples include aluminum nitride and boron nitride, with aluminum nitride being particularly preferred.
[0039] The heat insulating layer may be formed in the form of a powder as a spread powder layer or in the form of a plate on the bottom surface. The plate-shaped body is not limited to a dense plate, and a perforated plate or a perforated plate may also be used. When forming the heat insulating layer in the form of a powder, it is preferable to use the aluminum nitride powder obtained by the method of the present invention, since it will not become an impurity even if it is mixed into the product. The plate-shaped body may also be present on the side of the reaction vessel. When using aluminum nitride powder, it is also preferable to form the heat insulating layer by having it exist on the surface layer of the mixed powder filled in the reaction vessel.
[0040] The thickness of the heat insulating layer is suitably about 5 to 10 mm. The aluminum nitride obtained by the present invention is recovered as block-like lumps, but since they are weakly agglomerated, aluminum nitride powder can be easily obtained by crushing.
[0041] The above-mentioned crushing method is not particularly limited, and crushing means using media such as a ball mill, a vibration mill, or an attritor mill can be used, but it is preferable to use a crushing means that does not use media because the aggregation is not strong.Specific examples include a method using a grinding device such as a jet mill, a mass colloider, or a vibration mill that does not use balls.
[0042] The degree of the crushing is not particularly limited, but it is preferable to crush the aluminum nitride lumps obtained by the reaction so that the average particle size of the aluminum nitride lumps exceeds the average primary particle size of the aluminum nitride particles constituting the lumps and is 20 μm or less, preferably 4 to 20 μm, and more preferably 5 to 15 μm. In other words, by crushing to such a size, an aluminum nitride powder that is free from dusting and has excellent handleability is obtained.
[0043] The aluminum nitride powder thus obtained has a primary particle size of 3 μm or less, as will be described later, and can therefore be suitably used as a raw material for sintering.
[0044] Furthermore, a part of the aluminum nitride powder having the above primary particle size can be used without any problem as a diluent in the production method of the present invention. According to the manufacturing method of the present invention, since it utilizes a combustion synthesis reaction, external heating (forced heating) is not required. Moreover, by using a specified diluent, agglomeration is weak and high-quality aluminum nitride can be produced with a simple crushing process. These effects enable significant cost reduction and efficiency improvement compared to conventional manufacturing methods.
[0045] Thus, the method for producing aluminum nitride of the present invention is suitable for industrial-scale production, and makes it possible to provide aluminum nitride at low cost. [Aluminum nitride powder] The aluminum nitride powder obtained by the method of the present invention has a small average primary particle size of 3 μm or less, and is obtained by appropriately crushing aluminum nitride lumps obtained as weak agglomerates. Therefore, the aluminum nitride powder is obtained as agglomerated particles that maintain an appropriate agglomeration state while maintaining an average primary particle size equivalent to that of aluminum nitride powder obtained by conventional reduction nitridation methods.
[0046] Therefore, the aluminum nitride powder has high sinterability derived from the primary particle size, but can be handled as agglomerated particles with appropriate strength, produces little dust, and is advantageous in terms of the working environment.
[0047] That is, according to the present invention, there is provided an aluminum nitride powder comprising agglomerated particles of aluminum nitride primary particles having an average primary particle diameter of 3 μm or less, the agglomerated particles having an average particle diameter exceeding the average primary particle diameter and being 20 μm or less, preferably 4 to 20 μm, and more preferably 5 to 15 μm, and having a crushing strength of 300 MPa or less.
[0048] The aluminum nitride powder of the present invention preferably has a carbon concentration of 300 ppm by mass or less, and more preferably 200 ppm by mass or less. The aluminum nitride powder of the present invention has an oxygen content of 1.3 mass % or less, preferably 1.0 mass % or less. In the present invention, the average primary particle size is measured by a scanning electron microscope, and the average particle size of the agglomerated particles is measured by a particle size distribution meter (MT3000IIEX manufactured by Microtrackbell Co., Ltd.).
[0049] The agglomerated particles of the primary particles of aluminum nitride according to the present invention can be used for sintered bodies to produce aluminum nitride powder that is easy to handle and has good dispersibility in a solvent. In addition, the agglomerated particles of this aluminum nitride powder are weakly agglomerated, and due to the low crushing strength, the generation of new surfaces due to the collapse of the particles is small. Since the oxygen concentration of the powder is low after dispersion in a solvent, the thermal conductivity of the sintered body is high.
[0050] Such aluminum nitride powder can be produced, for example, by the production method described above. Since it is produced by a combustion synthesis reaction, the carbon concentration in the powder is originally low, and even if aluminum nitride powder produced by a reduction nitridation method is used as a diluent at start-up, the carbon concentration gradually decreases as the produced aluminum nitride is recycled and used as a diluent. The aluminum nitride powder of the present invention, which has such low carbon content, has an extremely high degree of whiteness.
[0051] In addition, since the aluminum nitride powder of the present invention can be shipped as an agglomerate having the above-mentioned average particle size, the powder does not scatter when mixed with a resin or a solvent, making it easy to handle, and since the powder has a low crushing strength, it is easy to disintegrate and disperse.
[0052] For this reason, the aluminum nitride powder of the present invention can be filled into resin packaging bags such as drums, PET cans, container bags, and paper bags and transported. The present invention can also provide such packages. EXAMPLES
[0053] The features of the present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples in any way. [Example 1] A metallic aluminum powder having an average particle size of 8 μm, an oxygen content of 0.05 mass%, and an impurity content excluding oxygen of 0.1 mass% was mixed with an aluminum nitride powder produced by a reduction nitridation method having an average primary particle size of 1 μm, an oxygen content of 0.8 mass%, and an impurity content excluding oxygen of 0.1 mass% in a ratio of 350 parts by mass to 100 parts by mass of the metallic aluminum powder to prepare a mixed powder. 2 The aluminum nitride was then packed in a uniform layer in a carbon reactor, and the mixture was then loaded into a pressure vessel. Nitrogen was introduced into the pressure vessel to set the pressure at 6 atm, and 700 W of power was applied to the ribbon heater for about 5 seconds to ignite the heater and initiate the nitriding reaction. After the reaction was completed, the aluminum nitride block was crushed in a vibration mill that did not use balls, and the resulting aluminum nitride block was crushed in a vibration mill that did not use balls, and then the ... 50 The aluminum nitride powder thus obtained had a particle size of 8.2 μm, an average primary particle size of 1 μm, and a crushing strength of 250 MPa. The oxygen concentration of the resulting aluminum nitride powder was 0.7 mass %.
[0054] The aluminum nitride powder obtained by the above method was used as a diluent, and the combustion synthesis reaction was repeated five times in the same manner as above, and the aluminum nitride powder was obtained by crushing in the same manner. As a result, the average particle size, average primary particle size, crushing strength, and oxygen concentration were almost the same. In the aluminum nitride powder obtained by circulating the generated aluminum nitride powder five times as a diluent, the carbon concentration was reduced to 180 ppm.
[0055] 5 parts by mass of yttrium oxide powder and 10 parts by mass of binder were added to 100 parts by mass of the above aluminum nitride powder, and a solvent was added and mixed, and the resulting slurry was formed into a sheet. The sheet compact was cut to a predetermined size and sintered at 1800°C to produce a sintered body. The density and thermal conductivity of the obtained sintered body were measured and found to be 3.321 g / cm 3 , 181W / mk.
[0056] [Example 2] In Example 1, the aluminum nitride powder was obtained by crushing in the same manner as in Example 1, except that the crushing after the nitriding reaction was carried out using a jet mill instead of a vibration mill. The aluminum nitride powder obtained was then molded into a sheet in the same manner as in Example 1, and a sintered body was produced and evaluated. The obtained powder was D 50 The aluminum nitride powder thus obtained had a particle size of 6.4 μm, an average primary particle size of 1 μm, an oxygen concentration of 0.8 mass%, and a crushing strength of 240 MPa. Furthermore, the density and thermal conductivity of the sintered body were measured, and found to be 3.34 g / cm 3 , 180W / mk.
[0057] [Example 3] In Example 2, the aluminum nitride powder was obtained by crushing in the same manner as in Example 2, except that the crushing energy using a jet mill after the nitriding reaction was reduced. The aluminum nitride powder obtained was molded into a sheet in the same manner as in Example 1, and then a sintered body was produced and evaluated. The obtained powder was D 50The aluminum nitride powder thus obtained had a particle size of 10.4 μm, an average primary particle size of 1 μm, an oxygen concentration of 0.8 mass%, and a crushing strength of 240 MPa. Furthermore, the density and thermal conductivity of the sintered body were measured, and found to be 3.34 g / cm 3 , 179W / mk.
[0058] [Comparative Example 1] An aluminum nitride powder was obtained in the same manner as in Example 1, except that the aluminum nitride powder for dilution was mixed with 100 parts by mass of the metallic aluminum powder to prepare a mixed powder. The obtained aluminum nitride powder was molded into a sheet in the same manner as in Example 1, and then a sintered body was produced and evaluated. The obtained powder had a D 50 The aluminum nitride powder thus obtained had a particle size of 26 μm, an average primary particle size of 5 μm, an oxygen concentration of 0.6 mass%, and a crushing strength of 340 MPa. Furthermore, the density and thermal conductivity of the sintered body were measured, and found to be 2.79 g / cm 3 , 95W / mk.
[0059] A similar nitriding reaction was attempted using the aluminum nitride powder obtained above as a diluent, but the flame did not propagate from the ignition agent and the reaction did not proceed. [Comparative Example 2] In Example 1, a nitriding reaction was carried out in the same manner as in Example 1, except that a powder with an average particle diameter of 15 μm was used as the aluminum nitride powder for dilution, and was mixed at a ratio of 300 parts by mass to 100 parts by mass of the metallic aluminum powder to prepare a mixed powder. However, a flame did not propagate from the ignition agent, and the reaction did not proceed.
Claims
1. A method for producing aluminum nitride by a combustion synthesis method, in which aluminum nitride powder having an average primary particle diameter of 3 μm or less is used as a diluent in a ratio of 150 to 400 parts by mass per 100 parts by mass of metallic aluminum powder, and the mixed powder is ignited and burned in a nitrogen atmosphere to obtain aluminum nitride having an average primary particle diameter of 3 μm or less, wherein the aluminum nitride lumps obtained by the combustion synthesis method are crushed to a size having an average particle diameter of 4 to 20 μm, and a part of the crushed lumps is used as the diluent.
2. 2. The method for producing aluminum nitride powder according to claim 1, wherein the average particle size of the metallic aluminum powder is 1 μm or more and less than 10 μm.
3. The bulk density of the mixed powder is 0.6 to 0.9 g / cm 3 The method for producing an aluminum nitride powder according to claim 1 or 2, wherein the content of the aluminum nitride powder is in the range of
4. The mixed powder is placed in a container having a base area of 0.3 m 2 The method for producing aluminum nitride powder according to any one of claims 1 to 3, wherein the above heat-resistant material is packed in a flat box in layers and ignited to combust the metallic aluminum powder.
5. The method for producing aluminum nitride powder according to claim 4, further comprising forming a heat insulating layer on the bottom surface of the flat box.
6. An aluminum nitride powder comprising aluminum nitride primary particles having an average primary particle diameter of 3 μm or less and agglomerated particles having a crushing strength of 300 MPa or less, the agglomerated particles having an average particle diameter of 4 to 20 μm.
7. The aluminum nitride powder according to claim 6, having a carbon concentration of 300 ppm by mass or less.
8. A package comprising a resin packaging bag filled with the aluminum nitride powder according to claim 6 or 7.
Citation Information
Patent Citations
Bed powder for firing aluminum nitride ceramics and firing method using same
JP1991199168A
Production of silicon nitride
JP1995081909A
Nitride containing isotopic nitrogen and its production
JP1995187619A
Production of aluminum nitride powder
JP1995309611A
Aluminum nitride powder with reduced ammonia odor and method for producing same
JP1996506794A